Optical and near-infrared IFU spectroscopy of the nuclear region of the AGN-starburst galaxy NGC 7582. Issue 4 (24th October 2017) - Ricci, T. V.; Steiner, J. E.; May, D.; Garcia-Rissmann, A.; Menezes, R. B.
Abstract: NGC 7582 is an SB(s)ab galaxy which displays evidences of simultaneous nuclear activity and star formation in its centre. Previous optical observations revealed, besides the H ii regions, an ionization cone and a gas disc in its central part. Hubble Space Telescope ( HST ) images in both optical and infrared bands show the active galactic nuclei (AGNs) and a few compact structures that are possibly associated with young stellar clusters. In order to study in detail both the AGN and evidence for star formation, we analyse optical (Gemini Multi-Object Spectrograph) and near-infrared (Spectrograph for Integral Field Observations in the Near Infrared) archival data cubes. We detected five nebulae with strong He ii λ4686 emission in the same region where an outflow is detected in the [O iii ] λ5007 kinematic map. We interpreted this result as clouds that are exposed to high-energy photons emerging from the AGN throughout the ionization cone. We also detected Wolf–Rayet features which are related to emission of one of the compact clusters seen in the HST image. Broad Hα and Br γ components are detected at the position of the nucleus. [Fe ii ] λ1.644 μm, H2 λ2.122 μm and Br γ flux maps show two blobs, one north and the other south from the nucleus, that seem to be associated with five previously detected mid-infrared sources. Two of the five He ii nebulae are partially ionized by photons from starbursts. However, we conclude that the main source of excitation of these blobs is the AGN jet/disc. The jet orientation indicates that the accretion disc is nearly orthogonal to the dusty torus.